(untitled) - Laird, Charlton (New York, 1953)
Contents: The miracle of the desart, the begats of the sons of Og,... Language is so entrancing that all sorts of people want to know about it, and yet, except for classroom texts which have limited usefulness outside the classroom.
Keywords: Language and languages,Ngôn ngữ và ngôn ngữ